The Rise of the Knowledge Graph - Martin, Sean; Allemang, Dean; Szekely, Ben (O'Reilly Media, Inc., 2021)
Businesses manage data to understand the connections between their customers, products or services, features, markets, and anything else that affects the business. With a knowledge graph, you can represent these connections directly to analyze and understand the compound relationships that drive business innovation. This report introduces knowledge graphs and examines their ability to weave business data and business knowledge into an architecture known as a data fabric . Authors Sean Martin, Ben Szekely, and Dean Allemang explain graph data and knowledge representation and demonstrate the value of combining these two things in a knowledge graph. You'll learn how knowledge graphs enable an enterprise-scale data fabric and discover what to expect in the near future as this technology evolves. This report also examines the evolution of databases, data integration, and data analysis to help you understand how the industry reached this point. Learn how graph technology enables you to represent knowledge and link it to data Understand how graph technology emphasizes the connected nature of data Use a data fabric to support other data-intensive tasks, including machine learning and data analysis Examine how a data fabric supports intense data-driven business initiatives more robustly than a simple database or data architecture.